Phenotypic characterisation of coagulase‐negative staphylococci isolated from blood cultures in newborn infants, with a special focus on Staphylococcus capitis. (10th July 2017) - Ehlersson, Gustaf; Hellmark, Bengt; Svartström, Olov; Stenmark, Bianca; Söderquist, Bo
Abstract: Aim: This Swedish study determined which species of coagulase‐negative staphylococci (CoNS) were found in neonatal blood cultures and whether they included Staphylococcus capitis clones with decreased susceptibility to vancomycin. Methods: CoNS isolates (n = 332) from neonatal blood cultures collected at Örebro University Hospital during 1987–2014 were identified to species level with matrix‐assisted laser desorption/ionisation time‐of‐flight mass spectrometry (MALDI‐TOF MS). The antibiotic susceptibility pattern of S. capitis isolates was determined by the disc diffusion test and Etest, and the presence of heterogeneous glycopeptide‐intermediate S. capitis (hGISC) was evaluated. Results: Staphylococcus epidermidis (67.4%), Staphylococcus haemolyticus (10.5%) and S. capitis (9.6%) were the most common CoNS species. Of the S. capitis isolates, 75% were methicillin‐resistant and 44% were multidrug‐resistant. No isolate showed decreased susceptibility to vancomycin, but at least 59% displayed the hGISC phenotype. Staphylococcus capitis isolates related to the strain CR01 displaying pulsotype NRCS‐A were found. Conclusion: Staphylococcus epidermidis, S. haemolyticus and S. capitis were the predominant species detected in neonatal blood cultures by MALDI‐TOF MS. The number of episodes caused by S. capitis increased during the study period, but no isolates with decreased susceptibility to vancomycin were identified. However, S. capitis isolates related to the strain CR01 displaying pulsotype NRCS‐A were found.